2011
DOI: 10.1002/path.2919
|View full text |Cite
|
Sign up to set email alerts
|

OCT2, SSX and SAGE1 reveal the phenotypic heterogeneity of spermatocytic seminoma reflecting distinct subpopulations of spermatogonia

Abstract: Spermatocytic seminoma (SS) is a rare testicular neoplasm that occurs predominantly in older men. In this study, we aimed to shed light on the histogenesis of SS by investigating the developmental expression of protein markers that identify distinct subpopulations of human spermatogonia in the normal adult testis. We analysed the expression pattern of OCT2, SSX2-4, and SAGE1 in 36 SS cases and four intratubular SS (ISS) as well as a series of normal testis samples throughout development. We describe for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…Therefore, our data support the common hypothesis of a different cell origin concerning spermatocytic seminoma and classic seminoma. 1,35 Although intratubular germ cell neoplasia unclassified is considered to be derived from developmentally arrested gonocytes, 2,[36][37][38] there is some controversy about the progenitor 39 Previous studies suspected primary spermatocytes 40 or spermatogonia 35,41 as progenitor cells. In our study, we found a strong expression of cancer testis antigens in spermatogonia and in spermatocytic seminoma, which is consistent with an origin of spermatocytic seminoma from spermatogonia, too.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data support the common hypothesis of a different cell origin concerning spermatocytic seminoma and classic seminoma. 1,35 Although intratubular germ cell neoplasia unclassified is considered to be derived from developmentally arrested gonocytes, 2,[36][37][38] there is some controversy about the progenitor 39 Previous studies suspected primary spermatocytes 40 or spermatogonia 35,41 as progenitor cells. In our study, we found a strong expression of cancer testis antigens in spermatogonia and in spermatocytic seminoma, which is consistent with an origin of spermatocytic seminoma from spermatogonia, too.…”
Section: Discussionmentioning
confidence: 99%
“…As far as spermatocytic tumour of older men is concerned, its gene expression profile -both at the transcript and protein level -resembles closely profiles of spermatogonia and early primary spermatocytes of the adult testis [26,27,70]. Accordingly, spermatocytic tumours do not express embryonic pluripotency genes and PGC/gonocyte specific markers, and markers of haploid spermatids (e.g.…”
Section: Immunohistochemical Markers Useful For Gct Diagnosis In Tissmentioning
confidence: 97%
“…Other immunohistochemical markers include SYCP1, NSE (neuron-specific enolase), CHK2, VASA, UTF1, FGFR3 or HRAS, and DMRT1 [26,27,30,46,71]. Recently, OCT2 was detected in a small subset of spermatocytic tumours and in A-dark spermatogonia [70], and in both cell types, OCT2 was found mutually exclusive with DMRT1 [75]. For diagnostic purposes in the clinics we suggest MAGE-A4 ( Figure 3) and DMRT1, which are the most robust immunohistochemical markers, as shown in Table 1.…”
Section: Immunohistochemical Markers Useful For Gct Diagnosis In Tissmentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed analysis of impaired spermatogenesis, three markers were chosen (Table 1), octamer-binding protein 2 (OCT2 (POU2F2)) for early spermatogonia (Lim et al 2011), sarcoma antigen 1 (SAGE1) for dividing and differentiating spermatogonia (Lim et al 2011), and mitosis-meiosis transition (Looijenga 2011), and SMAD3 for pachytene spermatocytes (Hentrich et al 2011).…”
Section: Antibodiesmentioning
confidence: 99%